Agroforestry practices, adoption factors, and livelihood contributions among smallholder farmers in Didu district, southwestern Ethiopia - Alemayehu Abera; Elias Bojago; Mamush Masha; Teshome Lidatu (Journal of Agriculture and Food Research)
Agroforestry (AF) has the potential to deliver for rural livelihoods, environmental sustainability, and climate change adaptation and mitigation. Little attention has been paid to smallholder farmers' perceptions, adoption levels with barriers, and influencing factors. This study examines how adoption is determined and the livelihood contribution of AF practices among smallholder farmers in Didu District, Southwestern Ethiopia. This study employed a mixed-method cross-sectional design. Using a multi-stage sampling procedure, 296 respondents (174 adopters and 122 non-adopters) were selected. The collected data were analyzed using thematic, descriptive, and inferential methods. Farmers adopted various AF practices in different home gardens (36 %), scattered trees in croplands (29.71 %), boundary tree planting (16 %), and hedgerows (2.29 %). The major barriers to AF adoption were the lack of extension services (98.3 %), limited land (97 %), and inaccessible markets (94 %). A binary logistic regression analysis was adopted, and it was positively influenced by wealth level (p < 0.01), level of education, size of the farm, slope of the farmland, extension relations, and farming experiences (p < 0.05) and negatively by distance from home to farmland (p < 0.05). Analysis of the net profit margin also showed that practice adopters had higher profitability rates than non-adopters (16.54 % vs. 9 %), and the AF reported economic benefits to smallholder farmers in the study area. The results showed that the diversified nature of smallholder farmers’ livelihoods in the area was largely supported by AF practices. Through AF practices, society has experienced diminished poverty levels together with enhanced food accessibility, and farmers have achieved better earnings and living conditions. This study proposes strategies to enhance AF as a base for enduring socioeconomic progress and supervision of natural resources.